Enzyme assisted direct air capture of carbon dioxide - Agnese Zaghini; Silke Flindt Badino; Stefanie Neun; Peter Westh (Carbon Capture Science & Technology, 2025)
Direct air capture (DAC) has been widely advocated as a key tool in the strive towards zero emissions. Here we present the first systematic data on enzyme assisted DAC and show that CO2 absorption rate tripled upon addition of carbonic anhydrase (CA) at micromolar concentrations, reaching a capture efficiency of 60%. We found that CA promoted high absorption efficiency as the flow rate was raised and we rationalized these observations based on molecular mechanism of enzyme assisted capture. Furthermore, measurements of absorption rates in KOH and carbonate with 1 μM CA showed comparable kinetics suggesting that enzyme application could offset kinetic advantages of hydroxides. These attributes may eventually pave the way for DAC in sorbents with low regeneration energies.